Bovine respiratory syncytial virus seroprevalence and risk factors in feedlot cattle from Córdoba and Santa Fe, Argentina = Seroprevalencia del virus respiratorio sincicial bovino y factores de riesgo asociados en engordes a corral de Córdoba y Santa Fe, Argentina - Ferella, Alejandra (2018)
Bovine respiratory syncytial virus (BRSV) is one of the causative agents of respiratory disease in cattle all over the world, leading to important economic losses. The aim of this work was to determine the seroprevalence of BRSV in feedlot cattle of Argentina and the risk factors associated with the disease. Results showed a high individual seroprevalence of 78.64% (95% confidence interval adjusted [CI] = 66.55–90.75%) against the virus. Positive association was found between the presence of high BRSV neutralizing antibody titers, and the following risk factors: cattle age, source of animals, presence of clinical respiratory signs and herd size. This work contributes to updating the understanding of its epidemiology in Argentinean feedlots and poses the need for reevaluating vaccination strategies against this virus in order to control infection and its impact on productivity.